The Effect of Using Snowball Throwing Method and SQ4R Method for Students’ Reading Comprehension Skill at SMA Negeri 1 Kuala Stabat - Ginting, Dameria; Manik, Sondang; Sinambela, Erika; Pasaribu, Arsen Nahum (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The objectives of this research are to identify the effect of the Snowball Throwing Method for students’ reading comprehension skill, to identify the effect of SQ4R Method for the students’ reading comprehension and to find out which method is the more significant between The Snowball Trowing Method and SQ4R Method in teaching reading comprehension. This research is an experimental quantitative research. The sample of this research were taken from grade twelve of SMA Negeri 1 Kuala students.  The data were gathered by using reading text multiple- choice test and were analysed by using t-test. The findings showed Snowball Throwing Method is significantly affecting the students’ reading comprehension skill in reading News Item Text. Since the tobs > ttable  (α= 0,05) df (58), or 9.44 >1.67155 (α =0,05) and SQ4R Method is also significantly affecting the students’ reading comprehension skill in reading recount text. Since the tobs > ttable  (α = 0,05) df (58), or 4.08 >1.67155 (α =0,05). In conclusion, the using of Snowball Throwing Method and SQ4R are significantly affect the students’ reading comprehension skill. And Snowball Throwing Method is the more significanlty effect the students’ reading comprehension skill than SQ4R method  in teaching news item text.